Polimorfismo Genético do Sistema HLA em uma amostra de Doadores Voluntários de Medula Óssea do Maranhão - Ferreira, Francileide Lisboa (2007)
The HLA system has as one of their main characteristics the high degree of genetic polymorphisms and it is known that the HLA molecules represent the main aloantígenos related to the rejection of grafts of solid organs and to the reaction of grafts against host in transplants of cells trunk hematopoietic. Those properties allow that the HLA alleles are used as instrument of characterization of the genetic composition of different people, once the allelic and haplotypes frequencies are characteristic of each ethnic group and population; for the study of HLA alleles associations with diseases and to evaluate the compatibility between donors and receivers of organs. In this study it was verified the allelic frequencies and the haplotype associations present in a sample of DVMO of the state of Maranhão and the power of these loci in exams of paternity. 1151 unrelated individuals, been born in Maranhão, were analyzed. All of the samples were analyzed by PCR - SSO method, in the Laboratory of Imunogenética and Molecular Biology (LIB) of UFPI. It was observed that the most frequent HLA-A genes were *02 (24,87%), *24 (9,87%), *01 (7,63%), *03 (6,96%) and *31 (6,71%). The largest frequencies for HLA-B alleles the were *44 (9,44%), *35 (9,19%), *15 (7,42%) and *07 (5,56%), and for HLA-DRB1 it was observed that *07 (12,81%), *13 (10,61%), *04 (8,07%), *11 (7,86%) and *03 (7,27%) were the most frequent. The haplotypes associations more frequents were HLA A*02 B*44 DRB1*07 (0,61%), HLA A*01 B*08 DRB1*03 (0,52%), HLA A*02 B*44 DRB1*13 (0,46%), HLA A*02 B*15 DRB1*04 (0,35%), HLA A*02 B*51 DRB1*13 (0,29%). The observed frequencies showed similar to those found in other Brazilian population studies and in comparison with other ethnic groups, there was larger similarity with the frequencies of European groups, following by the African. This result can be explained by the characteristics of the formation of the population from Maranhão that had effective contribution of three ethnic groups: the Indian, the white (mainly the Portuguese) and the black. The values of the Power of Exclusion and Power of Discrimination observed in the HLA loci in study were superior to the observed in common markers used for exams of exclusion of paternity.